The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.pain.2014.09.038
|View full text |Cite
|
Sign up to set email alerts
|

Classification of neuropathic pain in cancer patients: A Delphi expert survey report and EAPC/IASP proposal of an algorithm for diagnostic criteria

Abstract: Neuropathic pain (NP) in cancer patients lacks standards for diagnosis. This study is aimed at reaching consensus on the application of the International Association for the Study of Pain (IASP) special interest group for neuropathic pain (NeuPSIG) criteria to the diagnosis of NP in cancer patients and on the relevance of patient-reported outcome (PRO) descriptors for the screening of NP in this population. An international group of 42 experts was invited to participate in a consensus process through a modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…15 Although there has been a relative preponderance of neuropathic pain studies in the noncancer chronic pain populations, the generalizability of their findings to the cancer pain population has limitations. 16 An improved understanding and characterization of the clinical presentation of neuropathic cancer pain is, therefore, an important step in advancing its assessment and management. Furthermore, there are few reported data regarding cancer pain in Portuguese cancer care settings.…”
Section: Introductionmentioning
confidence: 99%
“…15 Although there has been a relative preponderance of neuropathic pain studies in the noncancer chronic pain populations, the generalizability of their findings to the cancer pain population has limitations. 16 An improved understanding and characterization of the clinical presentation of neuropathic cancer pain is, therefore, an important step in advancing its assessment and management. Furthermore, there are few reported data regarding cancer pain in Portuguese cancer care settings.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting knowledge synthesis will guide therapeutic intervention strategies in cancer pain management and thereby optimize health-related quality of life. • Evaluate use of standardized criteria such as the NeuPSIG guidelines or algorithm; [49,52] • Consensus (Delphi process and surveys) on the standardized operationalization of domain assessments, particularly psychological distr ess and incident pain;…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that screening with a validated tool may improve the sensitivity of neuropathic pain detection, as demonstrated in cancer pain studies with the Leeds Assessment of Neuropathic Pain Scale in Australia and the DN4 in Portugal [50,51]. Also, use of formal guidelines, such as the NeuPSIG guidelines or a standardized algorithm based on NeuPSIG criteria is likely to improve the accuracy of neuropathic pain diagnosis when compared to non-standardized clinical assessment [49,52].…”
Section: Pain Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Four specific criteria used are summarised in Table 1 A recent Delphi survey about the use and adaptation of the NeuPSIG criteria for NP diagnosis to be applied in cancer patients was conducted where an international group of 29 experts participated; the results showed experts agreed on criteria 1-3 of the NeuPSIG, whereas for the fourth criteria (confirmation of lesion affecting the somatosensory system from diagnostic test or imaging) experts suggested that a distinction had to be made whether history and existing exams could explain the cause of the pain [14]. We have combined these recommendations to outline a clinically relevant process to classify NP.…”
Section: Grading System For Neuropathic Painmentioning
confidence: 99%